Symbolic Displaying: Unggahan Mobil Mewah di Instagram - Hidayat, Christofer Hananta; Salman, Doddy (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2026)
Today's upper-class youth are increasingly active in showcasing their lifestyles on social media, particularly Instagram, as a means of asserting their social identity and prestige. One prominent form of representation is the ownership of luxury cars, which not only reflects economic achievement but also serves as a symbol of status and self-identity. This study aims to understand how the upper-class youth use luxury cars as a medium for self-image formation and how the audience responds to this representation. Using a descriptive qualitative approach, data was collected through in-depth interviews with a number of luxury car owners, then analysed using content analysis techniques to identify patterns of representation, symbolic meanings, and social interactions on Instagram. The results show that luxury cars are used to display prestige, hobbies, and achievements, build an exclusive image, and attract both positive interactions and criticism from the audience. Owning a luxury car also expands the social network and increases the digital visibility of its owners. The social media platform Instagram serves as a strategic space for the upper-class youth to express their social identity through material symbols. Today's upper-class youth are increasingly active in showcasing their lifestyles on social media, particularly Instagram, as a means of asserting their social identity and prestige. One prominent form of representation is the ownership of luxury cars, which not only reflects economic achievement but also serves as a symbol of status and self-identity. This study aims to understand how the upper-class youth use luxury cars as a medium for self-image formation and how the audience responds to this representation. Using a descriptive qualitative approach, data was collected through in-depth interviews with a number of luxury car owners, then analysed using content analysis techniques to identify patterns of representation, symbolic meanings, and social interactions on Instagram. The results show that luxury cars are used to display prestige, hobbies, and achievements, build an exclusive image, and attract both positive interactions and criticism from the audience. Owning a luxury car also expands the social network and increases the digital visibility of its owners. The social media platform Instagram serves as a strategic space for the upper-class youth to express their social identity through material symbols.